Comparative pharmacoepidemiological study of antihyperglycemic drugs utilization by patients with type 2 diabetes mellitus in Moscow - Marina F. Kalashnikova; Dmitrii Y. Belousov; Maria A. Kantemirova; Mikhail B. Antsiferov (Сахарный диабет)
Background. A pharmaco-epidemiological study comparing the dynamics of different anti-diabetic drugs in patients with type 2 diabetes mellitus (T2DM) in Russia was conducted using data from a diabetes registry.Objective. To assess and compare the frequency of the prescription of oral anti-diabetic medications (OAMs) and insulin and the average cost of anti-hyperglycaemic therapy with different OAMs in 2014 and 2011.Material and methods. A retrospective cohort study was conducted using national diabetic registry data from the city of Moscow. Data for 270,073 patients (≥18 years old) with T2DM registered by 31 December 2014 were analysed using international the ATC/DDD methodology. The average indicated and actual daily dosage ratio was calculated. The cost of anti-hyperglycaemic therapy for оne person/year was calculated.Results. There were no significant differences in prescribed OAMs between 2011 and 2014, despite the availability of new OAM classes (data for 2011 were published in «Diabetes mellitus», 2015, p. 32–46). The tendency to prescribe two groups of OAMs remained unchanged during the 4-year period (Metformin in 40% of patients and sulfonylurea derivatives, in combination or as a monotherapy, in 49.3%). The percentage of patients with T2DM who received insulin therapy increased from 10% in 2011 to 19.2% in 2014. The absence of a significant increase in the average cost of anti-diabetic therapy by 2014 can be explained by an increase in the prescription of different Russian generics for metformin, sulfonylurea derivatives and insulin, which were cheaper than foreign analogues by 30%–60%.Conclusions. The main trends in the treatment of patients with T2DM by 2014 included less frequent combination therapy with metformin and PSM and more frequent monotherapy or combination therapy with insulin. Despite the appearance of new OAM classes in the market, the overall consumption pattern in 2014 did not exceed 5%. The average cost of anti-diabetic therapy for one patient with T2DM in 2014 in Moscow was 7,727 rubles per year.